2003
DOI: 10.1046/j.1600-0668.2003.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Building characteristics, indoor air quality and recurrent wheezing in very young children (BAMSE)

Abstract: This study was conducted to examine the impact of building characteristics and indoor air quality on recurrent wheezing in infants. We followed a birth cohort (BAMSE) comprising 4089 children, born in predefined areas of Stockholm, during their first 2 years of life. Information on exposures was obtained from parental questionnaires when the children were 2 months and on symptoms and diseases when the children were 1 and 2 years old. Children with recurrent wheezing, and two age-matched controls per case, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 37 publications
3
78
1
2
Order By: Relevance
“…A "mouldy odor" was a significant risk factor for all asthma and allergic symptoms among children in Chongqing, consistent with some cohort studies [28,30]. "Condensation on window panes" was significantly associated with cough at night and rhinitis, consistent with the findings of a case-control study in Stockholm [44]. In Sweden, for doctor-diagnosed asthma and allergies, the significant risk dampness indices were floor moisture, damp stains and condensation [13].…”
Section: Association Between Asthma and Allergies And Dampnesssupporting
confidence: 83%
“…A "mouldy odor" was a significant risk factor for all asthma and allergic symptoms among children in Chongqing, consistent with some cohort studies [28,30]. "Condensation on window panes" was significantly associated with cough at night and rhinitis, consistent with the findings of a case-control study in Stockholm [44]. In Sweden, for doctor-diagnosed asthma and allergies, the significant risk dampness indices were floor moisture, damp stains and condensation [13].…”
Section: Association Between Asthma and Allergies And Dampnesssupporting
confidence: 83%
“…3,16,21,22,[24][25][26][42][43][44][45][46][47] An emerging literature does suggest that indoor allergens associated with asthma are related to the buildings in which people live. 10,11,[48][49][50][51][52] Considerable literature firmly establishes that the presence of cockroaches and rodents (i.e., pests) is associated with higher levels of asthma morbidity. 5,10,24,51,[53][54][55][56][57] Likewise, recent literature has highlighted the relationship between asthma morbidity and building types such as public housing; 54,58 mixed-use buildings, i.e., property containing both residential and commercial space; [59][60][61] and building size.…”
Section: Asthma and Indoor Allergensmentioning
confidence: 99%
“…[9][10][11]62,63 Lastly, indoor allergens and asthma morbidity have also been linked to building conditions; in particular older buildings and building violations in or near the residential building have been associated. 8,10,48,49,51,52 However, little explicit examination by building type and condition has occurred, especially in the USA.…”
Section: Asthma and Indoor Allergensmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it would probably not be feasible to ascertain exposure on an individual level. Nevertheless, several factors redeem the use of the outdoor meteorological measurements, (i) air conditioning was not very common in Austria and Germany during the study period, (ii) indoor absolute humidity is thus correlated with outdoor values even in winter (19), and (iii) there is evidence that skin locations typically covered with clothing (at least in winter) are nevertheless susceptible to temperature, humidity, and seasonal variation (12). Ultraviolet exposure, which could potentially have suppressed patch-test reactions, was not thought to have greatly influenced the results, as testing patients with recent ultraviolet exposure goes against international patch-testing guidelines (5) and a thorough Belgian study found no evidence of a correlation between ultraviolet intensity prior to patch testing and subsequent reactions (20).…”
Section: Discussionmentioning
confidence: 99%